Physical geology - Monroe, James S. (Thomson Brooks/cole, 2007)
Physical geology explorring the earth, Sixth Edition, doesn't just explain physical geology and its processes; it places that knowledge within the context of human experience by consistently emphasizing relevance, resources, and the environment